Inclusive Education Practices with Balinese Local Values of “Menyama Braya” in a Primary Bilingual School in North Bali - Ni Nyoman Padmadewi; I Made Sukma Adisetiawan Sukadana; Luh Putu Artini; Ketut Trika Adi Ana (Universitas Udayana, 2025)
This research explores the application of the Balinese philosophy of Menyama Braya or brotherhood in promoting inclusive education in a primary bilingual school in North Bali. Grounded in theories of multiculturalism and inclusivity, the study emphasizes the importance of acceptance, empathy, and cooperation among students from diverse backgrounds. Employing a phenomenological approach, data were collected through observations, in-depth interviews, discussions, and document analysis. The findings indicate that the integration of Menyama Braya principles fosters a cooperative learning environment where students, including those with special needs, engage meaningfully with their peers. This practice not only enhances tolerance and empathy but also supports the creation of culturally responsive educational spaces. Recommendations include incorporating Menyama Braya values into teacher education curricula to cultivate inclusive practices that celebrate diversity and ensure equitable access to quality education for all students. By embedding these local values into modern educational methodologies, schools can develop compassionate learning environments that embrace differences while promoting social harmony.